UZBEKISTAN AND JAPAN: NEW FACETS OF COOPERATION IN TOURISM - Ктайбеков С. М. (TARIXIY TADQIQOTLAR, 2025)
This article examines the main stages of cooperation between Uzbekistan and Japan, mutually beneficial agreements between these countries on the way to increasing the number of tourists from both countries, improving tourism infrastructure, preserving historical and cultural heritage, in addition, the investment potential of Uzbekistan for the implementation of new projects in the tourism sector is studied, and the statistics of Japanese tourists staying in Uzbekistan after independence are analyzed.